Profesionalitas Guru Agama Islam Pasca Program Profesi Guru di SD Negeri 01 Pemulutan Kabupaten Ogan Ilir - Annur, Saipul; Ibrahim, Ibrahim; Jannah, Miftahul; Fatmawaty, Fatmawaty (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the professionalism of Islamic Religious Education teachers after participating in the Teacher Professional Education Program at SD Negeri 01 Pemulutan, Ogan Ilir Regency, South Sumatra. This is a qualitative research using a descriptive approach. Data were collected through interviews, observation, and documentation study. The informants consisted of key informants (Islamic Religious Education teachers) and supporting informants (principal, school supervisor, and students), totaling 14 people selected using purposive sampling. Data analysis techniques included data collection, data presentation, verification, and conclusion drawing. Data validity was ensured through triangulation. The results showed an increase in the professionalism of Islamic Religious Education teachers after the program. This improvement was evident in professional competence, particularly in mastering subject matter and teaching strategies, as well as in more relevant educational qualifications. The use of technology in learning became more optimal, supported by effective communication skills with students, colleagues, and parents, thus strengthening the teacher's role as a professional educator